Phenotypic responses of the giant mussel Choromytilus chorus to prolonged upwelling conditions - Sebastián I. Martel; Nicolás J. Leppes; Nelson A. Lagos; Cristian A. Vargas; Marco A. Lardies (Aquaculture Reports, 2025)
Marine bivalve aquaculture is increasingly recognized as a sustainable alternative to mitigate potential animal protein shortages for human consumption. However, coastal aquaculture systems are susceptible to consequences of global change, including the projected increased duration of upwelling events within Eastern Boundary Upwelling Systems. These events can cause rapid environmental fluctuations that affect the biology of marine species including cultivable ones. This study investigates the phenotypic responses of the giant mussel Choromytilus chorus, an underutilized but promising shellfish species cultivated off the southern coast of Chile, to four laboratory-controlled combinations of temperature and pH conditions simulating the upwelling system they experience in farms. Our results show a remarkable capacity of this species to thrive in otherwise stressful environments. Notably, even under unprecedented warm and acidified conditions, juvenile individuals can effectively adjust their physiological state by elevating their rate of energy expenditure and increasing their feeding capacity. This plastic response allowed mussels to reduce the potentially negative consequences reported at an organismal level in other species, maintaining calcification and growth rates, and adjusting their periostracum's organic composition to an increased protein content under acidified conditions, thereby aiding shell production in a corrosive environment. Overall, our results underscore the potential for using suitably adapted cultivable species for food production in future changing scenarios.